α7 Nicotinic Agonist AR-R17779 Protects Mice against 2,4,6-Trinitrobenzene Sulfonic Acid-Induced Colitis in a Spleen-Dependent Way - Grandi, Andrea; Zini, Irene; Flammini, Lisa; Cantoni, Anna M.; Vivo, Valentina; Ballabeni, Vigilio; Barocelli, Elisabetta; Bertoni, Simona (Frontiers in Pharmacology, 2017)
The existence of a cholinergic anti-inflammatory pathway negatively modulating the inflammatory and immune responses in various clinical conditions and experimental models has long been postulated. In particular, the protective involvement of the vagus nerve and of nicotinic Ach receptors (nAChRs) has been proposed in intestinal inflammation and repeatedly investigated in DSS- and TNBS-induced colitis. However, in TNBS-induced colitis, the role of α7 nAChRs stimulation is still controversial and the potential contribution of α4β2 nAChRs has never been explored. Our aims were therefore to pharmacologically investigate the role played by both α7 and α4β2 nAChRs in the modulation of the local and systemic inflammatory responses activated in TNBS-induced colitis in mice and to assess the involvement of the spleen in nicotinic responses. To this end, TNBS-exposed mice were sub-acutely treated with various subcutaneous doses of highly selective agonists (AR-R17779 and TC-2403) and antagonists (methyllycaconitine and dihydro-β-erythroidine) of α7 and α4β2 nAChRs, respectively, or with sulfasalazine 50 mg/kg per os and clinical and inflammatory responses were evaluated by means of biochemical, histological and flow cytometry assays. α4β2 ligands evoked weak and contradictory effects, while α7 nAChR agonist AR-R17779 emerged as the most beneficial treatment, able to attenuate several local markers of colitis severity and to revert the rise in splenic T cells and in colonic inflammatory cytokines levels induced by haptenization. After splenectomy, AR-R17779 lost its protective effects, demonstrating for the first time that, in TNBS-model of experimental colitis, the anti-inflammatory effect of exogenous α7 nAChR stimulation is strictly spleen-dependent. Our findings showed that the selective α7 nAChRs agonist AR-R17779 exerted beneficial effects in a model of intestinal inflammation characterized by activation of the adaptive immune system and that the spleen is essential to mediate this cholinergic protection.